PENGARUH KOMPRES DAUN KOL TERHADAP PEMBENGKAKAN PAYUDARA PADA IBU POST PARTUM - Husna Maulida; aida fitriani; Era Wahyuni (Politeknik Kesehatan Kementerian Kesehatan Banten, 2022)
Breastfeeding is a natural event for a woman. However, breastfeeding problems that often arise in the early postpartum period (puerperal or lactation period) are breast engorgement. Breast engorgement is a blockage of milk due to the narrowing of the lactiferous ducts or by glands that are not emptied. The impact that will be caused if the breast milk dam is not resolved, namely mastitis and breast abscess, will occur. The use of cabbage or cabbage leaf compresses can be a non-pharmacological treatment. This study aimed to determine the effect of cabbage leaf compresses on breast swelling in postpartum mothers. The research method used is a quasi-experimental design. The design used is Posttest Only Control Group Design. The sample of this study was postpartum mothers who experienced breast swelling in PMB Erniati, North Aceh Regency. The number of respondents was 30 postpartum mothers who were divided into 2 groups (intervention and control groups). Each group consisted of 15 postpartum mothers. The results of statistical tests using the Mann Whitney U test p-value 0.000, which means that cabbage leaf compresses have an effect on breast swelling in postpartum mothers in PMB Erniati, North Aceh Regency.